Developing a pro-learning culture through international strategic alliances. (2016) - Erogul, Murat S.; Salamanca-Pacheco, Elizabeth; Barragan, Salvador
The international business environment is increasingly competitive; a better understanding of organisational learning and the learning curve is needed in international strategic alliances to gain competitive advantage. The paper examines a family firm's organisational learning through exogenous inter-organisational relationships and discovers the facilitation of a pro-learning culture. We find that learning through international strategic alliances increases endogenous learning opportunities among individuals, groups and the organisation. We contribute to the literature on how learning management capabilities and tasks from international strategic alliance partners facilitate creating, retaining and transferring knowledge within the organisation to improve and build new sources of competitive advantage. The implications for family firms who recognise the importance of creating a pro-learning culture develop the foundations of institutionalised learning that facilitate sustainable distinctive competencies.